POLITIK HUKUM UNDANG – UNDANG NOMOR 6 TAHUN 2014 TERKAIT DENGAN PENGUATAN HAK ULAYAT - Asrul, Asrul (Katalogis, 2017)
This thesis was to identify the Legal Politics of Law Number 6 Year 2014 Related with Customary Rigths in Indonesia. It was a juridicial normative research with legal materials as sources of study. The results of the research showed that the Legal Politics Of Law Number 6 Year 2014 Related with Customary Rights should have been referring to the prevailing laws and jurisprundence so that the development of democracy in the territory of Republik of Indonesia will be better and consistent with the autonomy right in the villages so that the legal politics and governmentship are acceptable to all levels of society.